An indirect comparison of intravenous and subcutaneous belimumab efficacy in patients with SLE and high disease activity. (25th April 2018) - Ramachandran, Sulabha; Parks, Daniel; Kurtinecz, Milena; Roth, David A; Alfonso-Cristancho, Rafael
Aim: To compare the efficacy of intravenous (IV) and subcutaneous (SC) belimumab plus standard therapy in patients with active, autoantibody-positive systemic lupus erythematosus and high disease activity (HDA).Patients & methods: An indirect treatment comparison using patient-level data of patients with HDA from three belimumab IV Phase III randomized controlled trials (BLISS-52 [BEL110751]; BLISS-76 [BEL110752]; Northeast Asia study [BEL113750]) and one belimumab SC randomized controlled trial (BLISS-SC [BEL112341]).Results: Similar efficacy results were identified between the belimumab formulations and greater improvements in efficacy endpoints were observed for both formulations compared with placebo.Conclusion: This indirect treatment comparison provides further evidence of the efficacy of belimumab IV and SC in patients with systemic lupus erythematosus and HDA, compared with standard therapy.